Interview with Andy Hoffman - Andrew J. Hoffman (economic sociology_the european electronic newsletter, 2020)
What is your motivation for teaching climate change in business classes? - I have a very clear answer to that question: If business does not solve the problem of climate change, it won't be solved. The market is the most powerful institution on Earth, business is the most powerful entity within it. So the market has to shift to address climate change. Many blame the market for climate change and the emergence of the Anthropocene, some call it the Capitalocene, and that's a fair criticism, but if we are going to address these issues, the market has to shift. [...]
Keywords: 300